The role of adrenergic agonists on glycogenolysis in rat hepatocyte cultures and possible involvement of NO - Hodis, Jiří; Kutinová-Canová, Nikolína; Potměšil, Petr; Kameníková, Ludmila; Kmoníčková, Eva; Zídek, Zdeněk; Farghali, Hassan (Physiological research, 2007)
Certain liver metabolic diseases point to the presence of disturbances in glycogen deposition. Epinephrine raises the cAMP level that activates protein kinase A leading to the activation of phosphorylase and glycogen breakdown. In the present report, we sought to investigate whether NO is produced during adrenoceptor agonist-induced glycogenolysis in rat hepatocytes in cultures. Isolated glycogen rich rat hepatocytes in cultures were used. NO production (NO2 -) was assessed under the effect of adrenergic agonists and adrenergic agonist/antagonist pairs, dibutyryl cyclic AMP sodiumpotassium salt (db-cAMP), NO synthase (NOS) inhibitors N?-nitro-L-arginine methyl ester (L-NAME), aminoguanidine (AG) and the NO donor S-nitroso-N-acetyl penicillamine (SNAP). The inducible NO synthase (iNOS) mRNA was examined by the reverse transcription-polymerase chain reaction (RT-PCR). Glycogenolysis was quantified by glucose levels released into medium. The amount of glucose and NO2 - released by hepatocytes was increased as a result of epinephrine, phenylephrine or db-cAMP treatments. The increase in glucose and NO2 - released by epinephrine or phenylephrine was blocked or reduced by prazosin pretreatment and by NOS inhibitors aminoguanidine and LNAME. iNOS gene expression was up-regulated by epinephrine. It can be concluded that glycogenolysis occurs through ?-adrenoceptor stimulation and a signaling cascade may involve NO production.
Keywords: hepatocyty; Nitric Oxide; Rats, Wistar; oxid dusnatý; potkani Wistar; polymerázová řetězová reakce s reverzní transkripcí; jaterní glykogen; adrenalin; Hepatocytes; Liver Glycogen; Epinephrine; Nitric Oxide Synthase; synthasa oxidu dusnatého; Reverse Transcriptase Polymerase Chain Reaction; Financing, Organized; Liver Diseases; Glycogenolysis; financování organizované; glykogenolýza; nemoci jater